Individuality in the Immune Repertoire and Induced Response of the Sponge Halichondria panicea - Schmittmann, Lara; Franzenburg, Sören; Pita, Lucía (Frontiers in Immunology, 2021)
The animal immune system mediates host-microbe interactions from the host perspective. Pattern recognition receptors (PRRs) and the downstream signaling cascades they induce are a central part of animal innate immunity. These molecular immune mechanisms are still not fully understood, particularly in terms of baseline immunity vs induced specific responses regulated upon microbial signals. Early-divergent phyla like sponges (Porifera) can help to identify the evolutionarily conserved mechanisms of immune signaling. We characterized both the expressed immune gene repertoire and the induced response to lipopolysaccharides (LPS) in Halichondria panicea, a promising model for sponge symbioses. We exposed sponges under controlled experimental conditions to bacterial LPS and performed RNA-seq on samples taken 1h and 6h after exposure. H. panicea possesses a diverse array of putative PRRs. While part of those PRRs was constitutively expressed in all analyzed sponges, the majority was expressed individual-specific and regardless of LPS treatment or timepoint. The induced immune response by LPS involved differential regulation of genes related to signaling and recognition, more specifically GTPases and post-translational regulation mechanisms like ubiquitination and phosphorylation. We have discovered individuality in both the immune receptor repertoire and the response to LPS, which may translate into holobiont fitness and susceptibility to stress. The three different layers of immune gene control observed in this study, - namely constitutive expression, individual-specific expression, and induced genes -, draw a complex picture of the innate immune gene regulation in H. panicea. Most likely this reflects synergistic interactions among the different components of immunity in their role to control and respond to a stable microbiome, seawater bacteria, and potential pathogens.